The Effectiveness of Health Education to Enhance Community Perception and Preferences Towards Honey for Healthcare - Widiyanto, Aris; Acob, Joel Rey Acob; Adriani, Rita Benya; Yuniarti, Tri; Halimah, Trisakti; Atmojo, Joko Tri (Public Health of Indonesia, 2025)
Background: Understanding the health benefits of honey has the potential to influence individual and family decision-making related to wellness and healthcare. Enhancing public knowledge through structured health education is therefore essential in shaping positive attitudes and informed choices regarding natural health remedies, such as honey. Objectives: This study aims to evaluate the effectiveness of health education in improving community perceptions and preferences regarding the use of honey in healthcare. Methods: This quantitative study was conducted in February 2024 in Ngargoyoso Village, Karanganyar Regency, using a quasi-experimental one-group pre-test and post-test design. An accidental sampling method was employed, resulting in a total of 40 respondents. Data analysis was performed using the Wilcoxon signed-rank test in SPSS version 22. The mean score of participants’ attitudes and preferences increased significantly from 15.22 ± 5.79 before the intervention to 21.87 ± 1.92 after the intervention. Results: The statistical analysis revealed a significant difference in scores between the pre- and post-intervention phases (p-value = 0.0001), indicating a positive impact of health education on participants’ perceptions and preferences regarding the use of honey in healthcare. Conclusion: The findings suggest that health education significantly enhances public understanding and acceptance of honey's health benefits, demonstrating its effectiveness in influencing perceptions and health-related choices within the community. Keywords: health education; honey; healthcare; perception; preference